2008
DOI: 10.1177/0886260508325495
|View full text |Cite
|
Sign up to set email alerts
|

The Perceived Impact of a Child Maltreatment Report From the Perspective of the Domestic Violence Shelter Worker

Abstract: The purpose of this study is to examine domestic violence shelter workers' perceptions of child maltreatment reporting. A sample of 82 professionals from domestic violence shelters across the United States participated in a survey focusing on a variety of different types of reports and the frequency of both positive and negative outcomes arising from these reports. Possible outcomes included in the study are damage to the relationship between the worker and the battered woman, disempowerment of the battered wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…It assessed participants' perceptions on: their IPV and CM Knowledge; Perceptions regarding IPV; Battered Parents; IPV and Reporting CM; Knowledge and Abilities Regarding IPV and CM; Effective Advocacy and Intervention; Training Received; and Workplace Policies. Many of its items were adapted from published instruments on actions taken in response to IPV and CM (e.g., Banks, Landsverk, and Wang 2008;Malik et al 2008;Mills and Yoshihama 2002;Saunders et al 1987;Steen 2009). Others were developed by the researchers to also assess providers' knowledge, perceptions, and beliefs about CM and IPV -the study's main focus, and for which no measures were identified within the peer-reviewed literature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It assessed participants' perceptions on: their IPV and CM Knowledge; Perceptions regarding IPV; Battered Parents; IPV and Reporting CM; Knowledge and Abilities Regarding IPV and CM; Effective Advocacy and Intervention; Training Received; and Workplace Policies. Many of its items were adapted from published instruments on actions taken in response to IPV and CM (e.g., Banks, Landsverk, and Wang 2008;Malik et al 2008;Mills and Yoshihama 2002;Saunders et al 1987;Steen 2009). Others were developed by the researchers to also assess providers' knowledge, perceptions, and beliefs about CM and IPV -the study's main focus, and for which no measures were identified within the peer-reviewed literature.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a study of all social service agencies in Virginia found that supervisors believe child protection investigation (CPI) workers possess (and only need) overall knowledge on a limited number of IPV related issues (Button and Payne 2009). Utilizing a national sample of IPV shelter workers, Steen (2009) found that these workers believed reporting the co-occurrence of IPVand CM would have adverse outcomes if the battered woman is the one abusing the child, or if the child only witnesses IPV.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nurses were then presented with 16 items assessing attitudes toward reporting exposure to IPV, which focused on the impact that reporting can have on abused women and their children, as well as on home visitors themselves. These items were adapted from questions used in previous studies of mandatory reporting of child abuse (Mathews et al., ; Steen, ) and IPV reporting (Gielen et al., ; Malecha et al., ; Sachs, Koziol‐McLain, Glass, Webster, & Campbell, ). The wording of the attitude items and response choices can be found in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Preliminary analyses revealed that no more than 5% of the data were missing for any variable. Given that all missing data techniques yield similar results when less than 5% of data are missing, 104 mean substitution was utilized to estimate missing values. Descriptive statistics (i.e., frequencies, percentages, means, and standard deviations) were used to describe demographic and study variables.…”
Section: Discussionmentioning
confidence: 99%